The promise of IL-1β modulation in NSCLC clinical context - Ghiringhelli, François; Rébé, Cédric (Frontiers in Immunology, 2026)
Emerging preclinical evidence challenges the long-standing assumption that Interleukin-1β (IL-1β) uniformly promotes non–small cell lung cancer (NSCLC). We show that, in the context of chemo-immunotherapy, IL-1β enhances anti-tumor immunity by inducing tumor-cell CXCL10 expression and recruiting CD8+ T cells, thereby sensitizing “cold” tumors to treatment. These findings contrast sharply with the failure of multiple CANOPY trials targeting IL-1β, suggesting that blockade may be effective only in prevention or early carcinogenesis. Instead, controlled IL-1β activation, guided by biomarkers and combined with chemotherapy plus PD-1 blockade, may represent a promising strategy to overcome resistance in established NSCLC.